Educator Knowledge of Early Childhood Development : Evidence from Eastern Nepal - Buck, Lindsey (World Bank, Washington, DC, 2020)
Early childhood is a crucial period for the cognitive, social, emotional, physical, and language development of children. Of the 200 million children who do not reach their developmental potential worldwide, 66 percent live in South Asia. This paper explores gaps in knowledge among educators in Eastern Nepal about the importance of early childhood. The results of a survey headteachers and teachers show that teachers often do not place enough weight on the importance of behaviors that contribute to the growth and development of children in early childhood. There are also large gaps in teachers' understanding and practice of classroom accommodations for children with disabilities. The paper illustrates that educators, who play a large role in children~^!!^s lives during early years, may be uninformed about the importance of early childhood development. The paper provides policy recommendations that can help policymakers target areas that lack understanding and improve early childhood development education and understanding among educators.